PEMBERDAYAAN USAHA KECIL DAN MENENGAH DALAM PEMBANGUNAN EKONOMI MASYARAKAT DI KELURAHAN MALALAYANG II KECAMATAN MALALAYANG KOTA MANADO - RAHMAYANTI, RIZKIA; ROMPAS, WELSON; PLANGITEN, NOVVA (Sam Ratulangi University, 2020)
ABSTRACTEmpowerment is a series of activity processes to strengthen and or optimize the empowerment of peoplewho have problems. The purpose of this study is how to empower small and medium businesses in theeconomic development of the community in Malalayang II Village, Malalayang District, Manado City.This research uses qualitative research. Data sources used are primary data and secondary data. Datacollection techniques used were interviews, observation and documentation. And analysis techniques usedaccording to data analysis techniques used according to Bogdan and Biklen 1982. The results of the studyshow that empowerment can increase the economic level of SMEs in the Malalayang II Village.Empowerment programs truly directed will be given directly to SMEs who need and who deserve to beempowered in order to develop their businesses into bigger and better businesses.Kata Kunci : Empowerment, UKM, Economic Development, Community